2021
DOI: 10.1007/s11109-021-09686-x
|View full text |Cite
|
Sign up to set email alerts
|

Promoting the Youth Vote: The Role of Informational Cues and Social Pressure

Abstract: Young voters, including college students, turnout less than older citizens-particularly in non-presidential elections. We examine two promising intervention strategies in the 2018 midterm elections: information cues and social pressure. Additionally, we consider whether voting information and social pressure to vote spread to others through social ties. Using a large-scale field experiment involving sections of a university-wide first-year writing seminar, we examine whether informational and social pressure p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 31 publications
(34 reference statements)
0
6
0
Order By: Relevance
“…Relationship between information publicity and subjective norms have been discussed in various context (Wang et al, 2018(Wang et al, , 2019. In the context of intention to participate in voting, Bergan et al (2021) studied the influence of information publicity and subjective norms in university students. Their study showed that information publicized to students and subjective norms significantly affects their intention to participate in voting provided that they have already overcome registration barriers.…”
Section: Information Publicity and Subjective Normsmentioning
confidence: 99%
See 2 more Smart Citations
“…Relationship between information publicity and subjective norms have been discussed in various context (Wang et al, 2018(Wang et al, , 2019. In the context of intention to participate in voting, Bergan et al (2021) studied the influence of information publicity and subjective norms in university students. Their study showed that information publicized to students and subjective norms significantly affects their intention to participate in voting provided that they have already overcome registration barriers.…”
Section: Information Publicity and Subjective Normsmentioning
confidence: 99%
“…Though social media researches for tourism have mainly focused on consumer behavior and satisfaction since 2010, several new ideas, such as big data, digital marketing, and online reviews, have lately been embraced for tourist studies (Lin et al, 2020). Social media disposition is viewed as a positive and negative influence (Bergan et al, 2021) on the outcomes of individuals, such as intentions and behaviors. In relation to subjective norms, which address the motivation dimension of individuals, information publicity is not a very powerful inducer of changes in intentions of individuals thus, researchers prefer to explain the weakness of relation in terms of intervening variables.…”
Section: The Moderating Role Of Social Media Dispositionmentioning
confidence: 99%
See 1 more Smart Citation
“…This effect is smaller than the effect of interventions providing specific and detailed information on the voting process. Recent experimental studies, which examined the effect of voting information on youth voter turnout (e.g., how to register to vote), found at least three times larger effects (Bennion & Nickerson, 2016;Bergan et al, 2021). Furthermore, students who participated in voting-related activities at a high school, including a get out the vote (GOTV) campaign and visiting elected officials, showed about 7.2 percentage points higher rates of voter turnout than comparison students (Gill et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…When it comes to improving youth voter turnout then, more direct interventions, including voting information interventions that aim to increase voters' understanding of the voting process (Bennion & Nickerson, 2016;Bergan et al, 2021;Gill et al, 2018) and/or electoral-level policy interventions-such as preregistration (Holbein & Hillygus, 2016), same day registration (Grumbach & Hill, 2022), and online registration (Yu, 2019)-might be far more effective. On the other hand, a broader curriculum targeting adolescents' non-cognitive skills-such as grit and task perseverance, which helps youth convert political motivation into actual participation (Holbein & Hillygus, 2020)-or other key psychosocial skills promoted by some high-achieving charter schools (Cohodes & Feigenbaum, 2021;McEachin et al, 2020) are also beginning to show promise.…”
Section: Introductionmentioning
confidence: 99%